Stress at Work : A Study of Organizational-Professional Conflict and Unmet Expectations - Lait, Jana; Wallace, Jean (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2002)
SummaryThis study examines how certain conditions of work affect human service workers’ job stress. We propose and assess a model of organizational-professional conflict to determine how professional and bureaucratic conditions of work influence service providers’ expectations and in turn their job stress. The model was tested using data from a survey of 514 human service providers in Alberta, Canada. The findings suggest that whether service providers’ expectations are met is critical in explaining job stress. Professional conditions of work relating to working relationships and client interactions are key to fulfilling service providers’ expectations, whereas bureaucratic conditions of work that reflect role conflict and excessive role demands are particularly stressful. An unexpected finding is that bureaucratization of procedures that may limit service workers’ control over their work does not contribute significantly to their job stress.